2011
DOI: 10.1038/nsmb.1978
|View full text |Cite
|
Sign up to set email alerts
|

Competing allosteric mechanisms modulate substrate binding in a dimeric enzyme

Abstract: Allostery has been studied for many decades yet it remains challenging to determine experimentally how it occurs at a molecular level. We have developed an approach combining isothermal titration calorimetry, circular dichroism, and nuclear magnetic resonance spectroscopy to quantify allostery in terms of protein thermodynamics, structure, and dynamics. This strategy was applied to study the interaction between aminoglycoside N-(6′)-acetyltransferase-Ii and one of its substrates, acetyl coenzyme A. It was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 51 publications
4
89
1
Order By: Relevance
“…Truncation of the R region results in a corresponding increase in the stability of the remaining ID NTD and an increase in its transcriptional activity. These results are suggestive of a general paradigm for allosteric control whereby the folding of disordered protein regions can control and be controlled by the folding of other ID regions (53,54). This strategy provides proteins with a general mechanism that can be utilized within all disordered segments, perhaps answering why ID sequences are found in such abundance in transcription factors and other cell signaling proteins (2).…”
Section: Discussionmentioning
confidence: 83%
“…Truncation of the R region results in a corresponding increase in the stability of the remaining ID NTD and an increase in its transcriptional activity. These results are suggestive of a general paradigm for allosteric control whereby the folding of disordered protein regions can control and be controlled by the folding of other ID regions (53,54). This strategy provides proteins with a general mechanism that can be utilized within all disordered segments, perhaps answering why ID sequences are found in such abundance in transcription factors and other cell signaling proteins (2).…”
Section: Discussionmentioning
confidence: 83%
“…This more structured NTD/AF1 shows increased affinity for important known CoFs. It is increasingly clear that ID is important for mediating allosteric control, as demonstrated theoretically and experimentally (91,92,100). By examining how the response of the protein ensemble to ligand can drive allosteric coupling, we have shown that the presence of one or more ID regions in a protein can modulate allosteric coupling between domains.…”
Section: Discussionmentioning
confidence: 86%
“…The internal motions associated with proteins are not only important for protein function (38)(39)(40)(41) but also because they act as crucial determinants of the ability of a protein to avoid aggregation (18,42). The present study has addressed this point in detail by showing the manner by which the native free energy landscape limits the accessibility of aggregation-prone regions of conformational space, thereby allowing the protein to maintain a soluble and functional state in solution.…”
Section: Discussionmentioning
confidence: 96%